2019
DOI: 10.1111/jch.13641
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal dipping status and the association of morning blood pressure surge with subclinical target organ damage in untreated hypertensives

Abstract: The clinical practice of hypertension management involves decision making based on absolute blood pressure (BP) levels, typically referring to the 24-hour, daytime, and nocturnal averages, though complementary indicators such as diurnal BP changes, nocturnal dipping status, and BP variability are also considered. In recognition of the normal circadian evolution of BP, the commonly recommended cutoffs for distinguishing between normotension and hypertension are 135/85 and 120/70 mm Hg for daytime and nocturnal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Recent studies indicate other adverse effects of morning hypertension. Gong changes did not depend on other BP indicators according to daily BP monitoring 5 . In patients with newly diagnosed AH who did not receive treatment, the relationship between BP variability and early systolic dysfunction of the left ventricle (LV) was found, even in cases with preserved LV ejection fraction (EF) 6 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent studies indicate other adverse effects of morning hypertension. Gong changes did not depend on other BP indicators according to daily BP monitoring 5 . In patients with newly diagnosed AH who did not receive treatment, the relationship between BP variability and early systolic dysfunction of the left ventricle (LV) was found, even in cases with preserved LV ejection fraction (EF) 6 .…”
Section: Introductionmentioning
confidence: 84%
“…Increased morning BP surge is defined to be associated with various factors, including aging, AH, DM, alcohol intake, smoking and stress. A series of investigations have demonstrated higher all-cause and cardiovascular mortality, regardless of the presence or absence of morning hypertension 2,4,5,13 . It was observed that there is an increased risk of stroke by 11% per each 10 mm Hg of morning BP surge increase 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding. The circadian variability of BP has been reported and exhibits a nocturnal dip with an early morning surge (Gong et al., 2019). Several studies have highlighted the importance of this morning surge in cardiovascular risk and end‐organ damage and even in normotensive patients an elevated morning surge is associated with increased risk of ventricular hypertrophy (Li et al., 2010; Xie et al., 2015; Ye et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Early morning is a high‐risk period in the day for the development of cardiovascular events, including stroke and ischemic heart disease 8,9 . Previous studies have reported that morning BP surge is associated with subclinical target organ damage 10 and that the surge is a strong predictor of stroke, coronary artery disease, and all‐cause mortality in hypertensive patients, as well as in the general population 11 . Nocturnal hypertension, defined as a nocturnal BP level of >120/70 mmHg as measured by ambulatory BP monitoring (ABPM) or home BP monitoring (HBPM) with a riser and non‐dipper BP pattern, is also associated with higher cardiovascular risk 8,12 .…”
mentioning
confidence: 99%